Pituitary Adenoma on 18F-Fluciclovine PET/CT. (January 2020) - Wang, Jiaqiong; Foley, Mark; Kuker, Russ
Abstract : Abstract: A 69-year-old man presented with lower urinary tract symptoms and prostate biopsy showed prostate cancer. 18 F-Fluciclovine PET/CT revealed abnormal increased radiotracer uptake within the prostate gland, and multiple osseous structures, suspicious for tumoral involvement. Incidentally, an expansile soft tissue density mass arising from sella turcica demonstrated increased radiotracer activity. MRI showed a lobulated enhancing mass centered in the sella and eroding into the sphenoid sinus. The differential diagnosis includes pituitary macroadenoma versus prostate cancer metastasis. The tumor was resected and the pathological diagnosis was pituitary adenoma.